Early resynchronization of follicular wave emergence among Nelore cattle using injectable and intravaginal progesterone for three timed artificial inseminations - Ataide Junior, Gilmar Arantes; Kloster, Anderson [UNESP]; Moraes, Emerson Guimaraes de; Motta, Igor Garcia; Claro Junior, Izaias; Vasconcelos, Jose Luiz M. [UNESP]; Ferraz, Priscila Assis; Nogueira, Guilherme de Paula [UNESP]; Pugliesi, Guilherme (Elsevier B.V., 2021)
Follicular dynamics and pregnancy per AI (P/AI) of cattle submitted to resynchronization 13 d after TAI using a progesterone (P-4) insert and supplementary injectable progesterone (iP(4)) were determined. There was synchronization of ovulation timing imposed (Day 0 = expected estrus; Experiment 1). On Day 13, animals were assigned to: control (only P-4 insert; 15 cows and 13 heifers) and iP4 (P-4 insert+100 mg iP(4); 13 cows and 12 heifers) groups, and submitted to daily ovarian ultrasonography and blood collection (Day 13 to Day 22). In Experiment 2, 760 suckled cows and 498 heifers were submitted to a TAI on Day 0 and assigned into control and iP4 groups on Day 13. In animals with luteolysis on Day 22, there was a second TAI on Day 24, and on Day 37 were subjected to the opposite treatments as imposed in first resynchronization procedure. On Day 37, there was pregnancy diagnosis in animals with functional CL. The third TAI was performed on Day 48. Day of follicular wave emergence did not differ between groups and parities. Dominant follicles were larger in cows than heifers, and in animals of the control group on Day 24. Greater P-4 concentrations were detected on Day 14 and Day 15 in the iP(4)-treated animals. Luteolysis occurred earlier in cows than heifers. Overall P/AI percentage as a result of second and third TAIs, regardless of parity, was greater in iP(4)-treated animals. In conclusion, females treated with a supplementary iP4 had a greater plasma P-4 concentration and P/AI, but there was no effect of iP(4) treatment on synchrony of timing of follicular wave.
Keywords: Doppler ultrasonography; Reproductive efficiency; Resynchronization; Short-acting progesterone